Determination of conditions for preventing chemical wear of induction furnace lining in the “cupola furnace – induction furnace” duplex process - Nikolaev, Denis; Selivorstov, Vadym; Dotsenko, Yuriy; Osypenko, Iryna; Kuznetsow, Eugene (Technology audit and production reserves, 2025)
The object of research is the melting of cast iron in the “cupola furnace – induction furnace” duplex process. The need to study such a duplex process is dictated by the condition of ensuring the required quality of cast iron in the event that a low-quality or uncontrolled charge is used. This condition cannot be met if the induction furnace is used as the only melting unit. But the problem is that in the process of induction melting of cast iron, in particular at the stage of overheating and holding the melt, a crucible reaction may begin, which leads to chemical wear of the lining. The need to reduce the carbon content in the melt discharged from the cupola furnace requires an increase in temperatures, which creates risks for the onset of a crucible reaction. Based on statistical calculations of cupola melting parameters, it was found that in the melt discharged from the cupola furnace into the induction furnace, the average carbon content is C = 3.47% with a standard deviation SC = 0.14%, and the average silicon content is Si = 2.05% with a standard deviation SSi = 0.21%. At the same time, with a probability of 96%, the carbon content is C = (3.33–3.75)%, and the silicon content corresponds to the range Si = (1.84–2.46)% with a probability of 98%. It was found that the equilibrium constant is in the range (0.15–0.21) with a probability of 97.8% at an average temperature T = 1355°C with a standard deviation of temperature ST = 6°C. With such melt parameters, which are supplied to the induction furnace, the risks of the onset of a crucible reaction do not arise. It was determined that even at temperature regimes sufficient to remove FeO, the risk of the onset of a crucible reaction is minimal. In order to ensure conditions that prevent the onset of a crucible reaction, the following recommendations should be followed for the content of carbon and silicon in high-temperature melting when the temperature is in the range T > 1480°C: C > 0.3% and Si < 0.3%. The results of the study can be used in the melting sections of foundries equipped with cupola furnaces and induction furnaces.